The impact of orthostatic intolerance on early ambulation following abdominal surgery in an enhanced recovery programme. Issue 4 (11th February 2022) - Hardy, Pierre‐Yves J‐P.; Tavano, Alessandro; Jacquet, Sophie V.; Monseur, Justine J.; Bastin, Marie‐Hélène L.; Kohnen, Laurent P.; Haumann, Alexandre E.; Joris, Jean L.
Abstract: Background: The prevalence of orthostatic intolerance on the day of surgery is more than 50% after abdominal surgery. The impact of orthostatic intolerance on ambulation on the day of surgery has been little studied. We investigated orthostatic intolerance and walking ability after colorectal and bariatric surgery in an enhanced recovery programme. Methods: Eighty‐two patients (colorectal: n  = 46, bariatric n  = 36) were included and analysed in this prospective study. Walk tests for 2 min (2‐MWT) and 6 min (6‐MWT) were performed before and 24 h after surgery, and 3 h after surgery for 2‐MWT. Orthostatic intolerance characterised by presyncopal symptoms when rising was recorded at the same time points. Multivariate binary logistic regressions modelling the probability of orthostatic intolerance and walking inability were performed taking into account potential risk factors. Results: Prevalence of orthostatic intolerance and walking inability was, respectively, 65% and 18% 3‐hour after surgery. The day after surgery, patients' performance had greatly improved: approximately 20% of the patients experienced orthostatic intolerance, whilst only 5% of the patients were unable to walk. Adjusted binary logistic regressions demonstrated that age ( p  = .37), sex ( p  = .39), BMI ( p  = .74), duration of anaesthesia ( p  = .71) and type of surgery ( p  = .71) did not significantly influence walking ability. Conclusion: Our study confirms that orthostatic intolerance was frequent (~ 60%) 3‐hour after abdominal surgery but prevented a 2‐MWT only in ~20% of patients. No risk factors for orthostatic intolerance and walking inability were evidenced.